Milk yield, rumen fermentation, and microbiota of Shami goats fed diets supplemented with spirulina and yeast - Alaa Emara Rabee; Moustafa Mohamed M. Ghandour; Ahmed M. Sallam; Osama Raef; Eman A. Elwakeel; Ebrahim A. Sabra; Adel M. Abdel-Wahed; Salah Abo Bakr; Hanan Saad ElSamahy; Amal Amin Hamed; Mebarek Lamara (AMB Express)
Abstract Microalgae and live yeast have gained interest in improving animal performance. This study evaluated the effect of supplementation with Spirulina platensis, Saccharomyces cerevisiae, or their combination on the in vitro and in vivo rumen fermentation, rumen microbiota, and milk yield and composition of lactating Shami goats. The in vitro experiment included four diets: non-supplemented basal diet consisted of Alfalfa hay and a concentrate feed mixture (C); basal diet supplemented with 1% Saccharomyces (Y) based on dry matter; basal diet supplemented with 1% Spirulina (A); and basal diet supplemented with 1% of a mixture of Saccharomyces and Spirulina (AY). In the in vivo experiment, twenty-one lactating goats were divided into three groups (n = 7) to receive one of three diets: C, A, and AY. Group AY had higher in vitro gas production, dry matter digestion (DMD), and volatile fatty acids (VFA) (p < 0.05). Milk yield and feed efficiency were higher in groups A and AY compared to group C. Group AY goats exhibited higher rumen total VFA, acetic, and propionic, while group A showed higher butyric acid. Lower predicted methane was observed in group AY. Groups A and AY showed distinctive microbial communities. The bacterial community was dominated by phylum Bacteroidota, and genera Prevotella and Rikenellaceae RC9 gut group, which were higher in the AY group. The archaeal community was dominated by the genus Methanobrevibacter, which had a lower prevalence in group AY. The combination of live yeast and Spirulina improved rumen fermentation and the milk yield; therefore, it could be used as a feed additive for lactating goats.